Associations between urinary phthalate metabolite concentrations and markers of liver injury in the US adult population. (October 2021) - Yu, Linling; Yang, Meng; Cheng, Man; Fan, Lieyang; Wang, Xing; Xu, Tao; Wang, Bin; Chen, Weihong
Highlights: Research on the joint toxic effect of various phthalates exposure on the liver is lacking. Several phthalate metabolites were significantly related to indicators of liver function tests. The combined effect of the phthalate mixture on the markers of liver injury was statistically significant. Abstract: Background: Phthalates have been largely used for years in varieties of products worldwide. However, research on the joint toxic effect of various phthalates exposure on the liver is lacking. Objectives: We aimed to assess exposure to phthalates on liver function tests (LFTs). Methods: This analysis included data on 6046 adults (≥20 years old) who participated in a National Health and Nutrition Examination Survey (NHANES) in 2007–2016. We employed linear regression and Bayesian kernel machine regression (BKMR), to explore the associations of urinary phthalate metabolites with 8 indicators of LFTs. Results: Di(2-ethylhexyl) phthalate (ΣDEHP) was found to be positively associated with serum alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP) (all P FDR  < 0.05). We found significant positive associations of ∑DEHP, mono-ethyl phthalate (MEP) and mono-(carboxyisononyl) phthalate (MCNP) with total bilirubin (TBIL) (all P FDR  < 0.05). ΣDEHP, mono-n-butyl phthalate (MBP), mono-(3-carboxypropyl) phthalate (MCPP) and mono-benzyl phthalate (MBzP) were negatively associated with serum ALB (all P FDR  < 0.05). The BKMR analyses showed a significantly positive overall effect on ALT, AST, ALP and TBIL levels with high concentrations of phthalate metabolites and a significantly negative overall effect on ALB and TP, when all the chemicals at low concentrations. Conclusions: Our results add novel evidence that exposures to phthalates might be adversely associated with the indicators of LTFs, indicating the potential toxic effect of phthalate exposures on the human liver.